2014
DOI: 10.1074/jbc.m113.526772
|View full text |Cite|
|
Sign up to set email alerts
|

Differentiation of Human Skeletal Muscle Stem Cells into Odontoblasts Is Dependent on Induction of α1 Integrin Expression

Abstract: Background: Human skeletal muscle stem cells (hSMSCs) can differentiate into bone and fat cells. Results: hSMSCs could also differentiate into odontoblasts but required an extracellular matrix scaffold and changes in their integrin profile. Conclusion:The present results identify an odontoblast differentiation pathway dependent on adhesion receptor expression. Significance: The data provide insight into how hSMSC adhesion receptors interact with the microenvironment to regulate lineage specification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Recently, we established conditions for efficient conversion of human muscle stem cells to an odontoblast lineage (48). We will use these cells to revisit our previous and current studies on rat fibroblast-like cells to determine the extent to which our findings are relevant in the human system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we established conditions for efficient conversion of human muscle stem cells to an odontoblast lineage (48). We will use these cells to revisit our previous and current studies on rat fibroblast-like cells to determine the extent to which our findings are relevant in the human system.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, a cytokine cocktail induced expression of MMP-3 that regulated cell proliferation and suppressed apoptosis in mouse ES cell-derived odontoblast-like cells (47) and human skeletal muscle stem cell-derived odontoblast-like cells (48). Interleukin-1β and the cytokine cocktail also induced MMP-3-regulated cell proliferation and suppressed apoptosis in partially purified rat dental pulp cells (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we established a proliferating dental pulp progenitor cell line, KN-3, from dental papilla cells of rat incisors 15) . We reported that KN-3 cells express high levels of alkaline phosphatase (ALP) activity, as well as runtrelated transcription factor 2 and dentin sialophosphop rotein [15][16][17] . In addition, we showed that KN-3 cells form mineralized nodules by treatment with ascorbic acid and β-glycerophosphate in an in vitro culture system.…”
Section: Ifn-γ Is An Important Proinflammatory Cytokine Thatmentioning
confidence: 99%
“…The localization and activation of APase in odontoblasts and pulpal fibroblasts or progenitor cells point to the role of APase in cell differentiation during dentine formation. Stem cell-based tooth regeneration is a promising approach to solving the problems of dentine caries and human skeletal muscle stem cells could also differentiate into odontoblasts but required an extracellular matrix scaffold and changes in their integrin profile that was evidenced by appearance of odontoblastic phenotypes [ 53 ]. Therefore, cellular responses of pulpal origin against dental caries seem evident.…”
Section: Discussionmentioning
confidence: 99%